Symptoms of Depression, Anxiety, and Stress in Students in Albania - Pilika, Anita; Maksuti, Pasho; Simaku, Artan (Open Access Macedonian Journal of Medical Sciences, 2022)
Depression, anxiety and stress are increasingly concerning phenomena in our society, with serious consequences on physical and mental health. The repercussions may be particularly devastating in particular population subgroups, such as female university students. The purpose of this study was to determine the levels of depression, anxiety, and stress among university students in Tirana. A cross-sectional study was conducted with a random sample of 570 students from the university students in Tirana. Information was collected on socio demographic and academic characteristics; symptoms of depression, anxiety, and stress. Female students manifest more symptoms of depression compared to male students. The higher level of symptoms of depression, anxiety and stress was found in the first academic years. Students with somatic disease exhibit higher scores compared to the rest of students. These findings highlight the need to adopt measures that address mental health, especially major depression, in female university students. Identifying the most frequent symptoms and finding a series of increased-risk and protective factors adds evidence to the existing scientific literature and allows efforts to be directed towards those experiences that are most frequent in female university students.